20,000 leagues under the sea - Verne, Jules, 1828-1905.; Armes, Stephen (New York : Grosset & Dunlap, 1996)
In the mid-nineteenth century, a French professor and his two companions, trapped aboard a fantastic submarine as prisoners of the deranged Captain Nemo, come face to face with exotic ocean creatures and strange sights hidden from the world above.
Keywords: Submarines (Ships) -- Fiction; Science fiction; Sea stories